2003
DOI: 10.1046/j.1439-0442.2003.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Ruminal Acidosis (SARA): a Review

Abstract: Subacute ruminal acidosis (SARA) is likely to arise when an easily palatable, high-energy diet meets a ruminal environment not adapted to this type of substrate. Increase of short-chained fatty acids (SCFA) will occur. Eventually, this may result in a transient nadir of ruminal pH below 5.5. Two situations are likely to represent the risk of SARA. First, fresh lactating cows are confronted with a diet considerably differing from that in the dry-period. A diet change carried out too rapidly or without proper tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
423
5
36

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(507 citation statements)
references
References 38 publications
19
423
5
36
Order By: Relevance
“…The growth rate was at a high performance level for this type of production and comparable to values seen in previous studies (Therkildsen et al, 1998;Jørgensen et al, 2007). Although several studies observed a better FCE when barleyand wheat-based concentrates were compared with sorghum and corn based (Kleen et al, 2003;Bengochea et al, 2005;Castillo et al, 2009) this was not the case in the present study. The actual batch of grain, its processing, degree of grinding and its proportion of the concentrate mixture are likely causes of the different outcome of these results.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The growth rate was at a high performance level for this type of production and comparable to values seen in previous studies (Therkildsen et al, 1998;Jørgensen et al, 2007). Although several studies observed a better FCE when barleyand wheat-based concentrates were compared with sorghum and corn based (Kleen et al, 2003;Bengochea et al, 2005;Castillo et al, 2009) this was not the case in the present study. The actual batch of grain, its processing, degree of grinding and its proportion of the concentrate mixture are likely causes of the different outcome of these results.…”
supporting
confidence: 88%
“…This is in agreement with our previous finding (Jørgensen et al, 2007) that despite a significant difference in LA status between two groups of concentrate-fed young bulls there was no significant differences in rumen wall and papillae characteristics at slaughter. Furthermore, despite a high starch level (Kleen et al, 2003) and a low roughage intake (Kreikemeier et al, 1990) on the one side, and bloat (Ramsey et al, 2002), ruminal acidosis (Galyean and Rivera, 2003), pathological rumen wall characteristics (Scanlan and Hathcock, 1983) and LA (Jørgensen et al, 2007) on the other side are somewhat linked (Smith, 1944;Jensen et al, 1954;Tamate et al, 1973), this is not a straight forward relation. However, when a more intensive grain feeding was compared with a less intensive feeding it caused a higher incidence of post mortem evaluated ruminal lesions and also a higher incidence of LA (Smith, 1944;Jensen et al, 1954;Tamate et al, 1973).…”
mentioning
confidence: 99%
“…Thus, in response to acidosis, the rate of metabolism and proliferation of stratified squamous epithelium increase dramatically, resulting in premature transition of cells into the keratinous layer, a condition known as parakeratosis (Kleen et al, 2003;Steele et al, 2011;Plaizier et al, 2012). All animals that received any type of concentrate had a darker colour than those fed on alfalfa.…”
Section: Digestive Tract Characteristicsmentioning
confidence: 99%
“…Albeit all values observed in this experiment were within the normal range, Alfalfa lambs had significantly higher blood pH values than the rest of the animals by mid-fattening period, but these differences were not maintained until the end of the period. This perhaps could be related to increased keratinisation of ruminal mucosa or its development in the final stages of the fattening period, which may reduce acid absorption from the rumen (Krehbiel et al, 1995;Kleen et al, 2003). Therefore, the development of parakeratosis as a result of a chemical injury, such as that caused by acidosis, may protect the animals against a continuous drop in blood pH.…”
Section: Digestive Tract Characteristicsmentioning
confidence: 99%
“…As a consequence, the ruminant microbial ecology and systemic metabolic state will change because of the rapid fermentation and subsequent excessive organic acids accumulation, and such animals are likely to suffer metabolic disorders such as acidosis, fatty liver, laminitis and even systemic inflammation (Alegre et al, 1988;Kleen et al, 2003;Plaizier et al, 2008;Dong et al, 2011;Tao et al, 2014). Our previous studies also showed that long-term feeding of a 65% high concentrate (HC) diet to lactating dairy goats led to subacute ruminal acidosis (SARA) and disruptions of mucosal barrier in the hindgut (Dong et al, 2013;Tao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%